Exploring robotic process automation adoption among accounting professionals in South Africa: Application of the UTAUT model - Thipe, Katlego; Gold, Nusirat Ojuolape; Coovadia, Husain (Journal of Accounting and Investment, 2026)
Research aims: The rapid advancement of robotic process automation (RPA) technologies presents significant transformation opportunities for the accounting profession, yet adoption rates remain inconsistent across different contexts. This study investigates factors influencing RPA adoption among accounting professionals in South Africa, employing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework.Design/Methodology/Approach: Using descriptive and inferential statistics, the study analysed quantitative and qualitative data gathered from 100 accounting and auditing professionals.Research findings: Findings revealed Social Influence as core predictor while skills and training gaps, resistance to change, and resource constraints were notable barriers. A significant awareness-implementation gap was also observed for RPA knowledge versus usage.Theoretical contribution/Originality: This study contribes theoretically by demonstrating that social legitimation may outweigh technical performance in professional settings within emerging markets, a contexts where peer validation and collective professional endorsement are crucial. By theorizing awareness-implementation paradox, it noted that attitude and knowledge are vital yet, insufficient for behavioural change. Additionally, it provides context-sensitive validation of UTAUT constructs from an emerging economy.Practitioner/Policy implication: The findings reinforce technology-centric adoption, with professional services contexts exhibiting unique dynamics. Overall, it highlights prioritizing social factors, management endorsement and peer advocacy as implementation strategies for RPA adoption over technical features. These findings provide evidence-based guidance for organisations and professional bodies seeking to advance RPA adoption within the South African accounting professional context.